Audio beam system : projecting sound in laser precision - Chan, Chun Yan. (2010)
A communication system is designed to transmit and receive information. The information to be sent is generally superimposed by modulation onto an electromagnetic wave called the carrier. It is then transmitted to a receiver where the information is recovered by demodulation. In this project, laser communication system will be implemented by projecting sound in laser precision to allow sound to be transmitted in a point-to-point manner over free space. The transmitter will introduce frequency modulation technique known as slope modulation while the receiver uses slope detection to demodulate. Frequency modulation is being used as variations in frequency causing its resilience to signal level variations. FM modulation has a higher signal to noise ratio making it suitable for high quality broadcast transmissions. Hardware circuitry for both transmitter and receiver will be designed and implemented, together with a laser points to perform point-like communication. Multiple transmitters and receivers can be built to reproduce a truly surround illusion of the source environment. Through this project a cheap and efficient way to transmit audio signal over free space will be highlighted.